Moral Panics, the Media and the Law in Early Modern England
XI, 279 p. 7 illus.
Keywords: An exploration of links between opinion and governance in Early Modern England, studying moral panics about crime, sex and belief. Hypothesizing that media-driven panics proliferated in the 1700s, with the development of newspapers and government sensibility to opinion, it also considers earlier panics about cross-dressing and witchcraft.